A histopathologic and immunohistochemical study on liquification of human adipose tissue ex vivo - Huebner, Nina-Fee; Horch, Raymund E.; Polykandriotis, Elias; Rau, Tilman; Dragu, Adrian (Aesthetic Plastic Surgery, 2014)
This preliminary ex vivo study aimed to clarify the pathophysiologic mechanisms of fat tissue depletion by subcutaneous drug application. Therefore, the lipolytic effects of phosphatidylcholine plus deoxycholate (Lipostabil) (L) and of deoxycholate (DC) alone were compared with those of sodium chloride (NaCl) and hydrogen peroxide (H2O2) as control agents. The study enrolled 10 patients receiving abdominoplasty. The treatment periods for each sample and solution were 1, 3, 5, and 7 h. The samples were analyzed morphologically using hematoxylin-eosin (H&E) staining and also immunohistochemically using Caspase 3 and tumor necrosis factor (TNF)-alpha. Morphologic changes were seen best after 5 h of application time. Except for NaCl, all the samples in the H&E staining showed marked damage of adipocyte cell membranes, with the greatest disruption of normal cell architecture after hydrogen peroxide (H2O2) application. Immunohistochemistry using TNF-alpha showed positive results for the deoxycholate and Lipostabil samples and highly positive results for the H2O2 sample. Data from this study indicate that Lipostabil and deoxycholate induce pathways of cell necrosis involving TNF-alpha. These short-term experiments indicate that Lipostabil affects fat tissue in the way of a chemical-toxic destruction rather than via a physiologically induced, programmed cell death.
EVALuna2:6587